Food (in) Security Among the Community at the Indonesia-Malaysia Border at Pandemic COVID-19 era: A Human Security Perspective - Sidik Jatmika; Yogaswara Aji Pratama; Dama Rifki Adhipramana (Mandala: Jurnal Ilmu Hubungan Internasional, 2021)
This article aims to examine food security issue among the community at the Indonesia - Malaysia border at Pandemic COVID-19 era by using the theory of interdependence and the human security approach. The study is conducted using a qualitative research method to collect and analyze both primary and secondary data. Primary data were obtained through official documents and an in-depth interview with key informants among Indonesia households of the communities in Indonesia - Malaysia border and local leaders. Meanwhile, published materials and online documents such as books, journal articles and reports served as a secondary source of data. The findings indicate that pandemics COVID-19 create vulnerability to food insecurity at border community. Realizing this fact, the government should consider adopting the human security concept, which emphasizes community empowerment as a framework in policymaking, with the aims to eradicate food insecurity among vulnerable households and to ensure the well-being of every Indonesian.